Financial Performance of Innovation Investment in Specialized‎SMEs Under A Digital Business Environment: A Comparative‎Analysis of China and Thailand (2019-2024)‎ - Fu, Yanwei; Duan, J. Yunlong (International Journal of Accounting and Economics Studies, 2025)
This study investigates the financial performance implications of innovation investment in specialized small and medium enterprises (SMEs) ‎operating within digital business environments, comparing China and Thailand from 2019-2024. Using a mixed-methods approach, this ‎research employs Partial Least Squares Structural Equation Modeling (PLS-SEM) and Data Envelopment Analysis (DEA) to analyze primary survey data from 284 specialized SMEs (184 Chinese, 100 Thai) and secondary financial data covering the pre- and post-digital trans-‎formation periods. The Sustainable Digital Transformation (SDT) framework is integrated with the Technology-Organization-Environment ‎‎(TOE) model to examine innovation investment impacts. Results reveal significant positive relationships between innovation investment and ‎financial performance in both countries, with Chinese SMEs demonstrating 23% higher ROI from digital innovation investments compared ‎to Thai counterparts. Digital transformation mediates 68% of the innovation investment-performance relationship in China versus 45% in ‎Thailand. Manufacturing SMEs in both countries outperform service-sector SMEs by 31% in innovation-driven financial performance. The ‎study is limited to two countries and may not generalize to other emerging economies. Cultural and institutional differences between China ‎and Thailand provide valuable insights but limit broader applicability. Practical implications: Before applying innovation strategies, SME ‎managers need to invest in digital infrastructure. Government-pushed policies that encourage digital transformation yield 2.3× more productive innovation investment. It is the first comprehensive comparative study examining the financial performance of innovation investment in ‎China and Thailand’s specialized SMEs for the critical digital transformation period of 2019-2024, providing theoretical and practical implications to emerging market SMEs‎.